Al-Qur'an-Based Character Education In Facing The Moral Crisis Of The Younger Generation - Muhammad Ryan Anwar (Al-Hudaya: Jurnal Ilmu Al-Qur'an dan Pendidikan, 2025)
The growing moral crisis among today's young generation demands an educational system capable of instilling moral and spiritual values as the foundation of character formation. Qur'an-based character education serves as a strategic solution in shaping students with noble character and integrity. This study aims to describe the implementation of Qur'an-based character education in shaping students' morality and to analyze its impact on their behavior and academic culture in higher education. The research employed a descriptive, qualitative method with a field study approach, collecting data through in-depth interviews with 15 students actively involved in Qur'anic mentoring activities. Thematic analysis was conducted to identify the process of internalizing Qur'anic values and their manifestation in campus life. The findings reveal that the most dominant internalized Qur'anic values include honesty (ṣidq), responsibility (amānah), discipline (iltizām), social care (ta'āwun), patience (ṣabr), and humility (tawāḍu'). These values play a significant role in shaping students' integrity, discipline, empathy, and social awareness. Furthermore, the implementation of Qur'anic values contributes to creating a more ethical, harmonious, and spiritually grounded academic culture. Therefore, Qur'an-based character education has proven effective in addressing the moral crisis among youth by fostering a balance between intellectual, emotional, and spiritual intelligence. This model is expected to produce a Qur'anic generation with noble character, strong social responsibility, and the ability to contribute positively to modern society.